Patients whom neurologists find difficult to help. Issue 12 (16th November 2004) - Carson, A J; Stone, J; Warlow, C; Sharpe, M
Abstract : Background: All doctors recognise that some patients are more "difficult to help" than others, but the issue has received little systematic investigation in neurological practice. Objective: To test the hypothesis that patients whose symptoms were less explained by organic disease would be perceived as more difficult to help. Methods: In a consecutive series of 300 new neurology outpatients, neurologists indicated on four point Likert-type scales how "difficult to help" they found the patient and to what extent the patient's symptoms were explained by organic disease. The patients' demographics, health status, number of somatic symptoms, and mental state were also assessed. Results: The neurologists rated 143 patients (48%) as "not at all difficult" to help, 111 (37%) as "somewhat difficult", 27 (9%) as "very difficult", and 18 (6%) as "extremely difficult". A logistic regression model was constructed and the hypothesis that patients whose symptoms were less explained by organic disease would be perceived as more difficult to help was supported. The only other measured variable that contributed to perceived difficulty was physical disability, but it explained only a small amount of the variance. Conclusions: Neurologists find patients whose symptoms are not explained by organic disease more difficult to help than their other patients.